Single Port 11 mm Laparoscopic Hysterectomy Performed on a 32-Year-Old Female with Adhesive Disease - Greg J. Marchand; Ali Azadi; Sienna Anderson; Stacy Ruther; Sophia Hopewell; Giovanna Brazil; Katelyn Sainz; Hannah Wolf; Alexa King; Janelle Vallejo; Kelly Ware; Kaitlynne Cieminski; et al. (Hindawi Limited, 2020)
In the field of minimally invasive surgery, there is constant drive to devise and execute the most minimally invasive surgeries possible. By the very nature of laparoscopy and robotic surgery, what one can accomplish with several ports of a given size will invariably be studied and attempted with fewer ports and with ports of smaller sizes. Although more complex pathology may require a more invasive approach, surgical cases without serious complicating factors may be amenable to extremely minimally invasive procedures. We report one such case where a 32-year-old female suffering from adenomyosis and endometriosis was able to receive a laparoscopic single-port hysterectomy and bilateral salpingo-oophorectomy through a single 11 mm port created with a blunt trochar.